OP0278 IDENTIFICATION OF PARAMETERS ASSOCIATED WITH A DIAGNOSTIC DELAY IN AXIAL SPONDYLOARTHRITIS: RESULTS FROM THE EUROPEAN MAP OF AXIAL SPONDYLOARTHRITIS (EMAS). (2nd June 2020) - Garrido-Cumbrera, M.; Navarro-Compán, V.; Bundy, C.; Mahapatra, R.; Makri, S.; Correa-Fernández, J.; Christen, L.; Delgado-Domínguez, C. J.; Poddubnyy, D.
Abstract : Background: Early diagnosis of Axial Spondyloarthritis (axSpA) is crucial for timely access to specialist care and effective treatment. Objectives: To assess the current diagnostic delay in axSpA and identify the parameters associated with increased diagnostic delay in a European sample. Methods: Data from unselected patients participating in the European Map of Axial Spondyloarthritis (EMAS) study through an online survey (2017- 2018) across 13 countries were analysed. Mean differences in diagnostic delay were analysed using Mann-Whitney and Kruskal-Wallis tests, among sociodemographic and disease-related factors. A multivariate linear regression analysis was carried out to identify the relative weight of the associated parameters in determining diagnostic delay. Results: 2, 846 patients participated in EMAS. Mean age was 43.9 years, 61.3% were female, 48.1% had a university degree, and 53.9% were employed. Of the 2846 participants, 2652 provided information for calculating diagnostic delay. Mean age at symptom onset was 26.6 ± 11.1, mean age at diagnosis was 33.7 ± 11.5, and mean diagnostic delay was 7.4 ± 8.4 (Fig. 1 ). The following variables were associated with longer diagnostic delay in the bivariate analysis: older age, female gender, being diagnosed by a rheumatologist (Table 1 ). In the multivariate regression analysis younger age at symptom onset, number of HCPs seen before were associated with diagnostic delay (Table 2 ). Conclusion: In this large sample of axSpA patients from 13 different European countries, the average diagnostic delay was more than seven years. The fact that one of the most strongly associated parameters to diagnostic delay was number of HCPs seen before diagnosis suggests the need for urgent action to reduce incorrect referrals to shorten the patient journey to diagnosis across Europe. Acknowledgments: Funded by Novartis Pharma AG Disclosure of Interests: Marco Garrido-Cumbrera: None declared, Victoria Navarro-Compán Consultant of: Abbvie, Lilly, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, MSD, Lilly, Novartis, Pfizer, UCB, Christine Bundy Grant/research support from: Has received unrelated honoraria from Abbvie, Celgene, Janssen, Lilly, Novartis, and Pfizer., Raj Mahapatra: None declared, Souzi Makri: None declared, José Correa-Fernández: None declared, Laura Christen: None declared, Carlos Jesús Delgado-Domínguez: None declared, Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB